RAPPORT SOCIAUX ENTRE FILLES-MERES ET LEURS PARENTS A KISANGANI - Itindi, Jérôme Waliala Apataki; Désiré Isetcha Tawiti; Taylor Athongo; Pierre Basuli Wemeli; Jean Akaluko Towowo (IJRDO - Journal of Social Science and Humanities Research, 2019)
The survey of the functions of the conflicts presents these as inherent to all social life. The conflicts also constitute a variable of life in society and they take varied shapes and distinguish themselves by the nature of their stakes. For this theory schooling the urbanization and the Christian religion weaken the traditional structures by a laxity of the control of the adults (parents or guardians) on the cadets or the young. This article shows how presents itself the social reports between the girls-mothers and their parents show why the girl-mother phenomenon generates him of the problems within the families to identify the indicators of the girl-mother phenomenon and offer the tracks of the solutions also.